Sea-to-air and diapycnal nitrous oxide fluxes in the eastern tropical North Atlantic Ocean - Kock, A.; Schafstall, J.; Dengler, M.; Brandt, P.; Bange, H. W. (Biogeosciences, 2012)
Sea-to-air and diapycnal fluxes of nitrous oxide (N2O) into the mixed layer were determined during three cruises to the upwelling region off Mauritania. Sea-to-air fluxes as well as diapycnal fluxes were elevated close to the shelf break, but elevated sea-to-air fluxes reached further offshore as a result of the offshore transport of upwelled water masses. To calculate a mixed layer budget for N2O we compared the regionally averaged sea-to-air and diapycnal fluxes and estimated the potential contribution of other processes, such as vertical advection and biological N2O production in the mixed layer. Using common parameterizations for the gas transfer velocity, the comparison of the average sea-to-air and diapycnal N2O fluxes indicated that the mean sea-to-air flux is about three to four times larger than the diapycnal flux. Neither vertical and horizontal advection nor biological production were found sufficient to close the mixed layer budget. Instead, the sea-to-air flux, calculated using a parameterization that takes into account the attenuating effect of surfactants on gas exchange, is in the same range as the diapycnal flux. From our observations we conclude that common parameterizations for the gas transfer velocity likely overestimate the air-sea gas exchange within highly productive upwelling zones.